The Effect of Reflection-Based Questioning Approach in Reading Comprehension of Recount Text - Elina Wilujeng; Arik Susanti (Journal of English Language and Education, 2026)
Reading comprehension is vital for secondary students to master functional texts like recount stories. However, a gap remains in implementing effective questioning strategies that move beyond rote learning to deeper understanding. This study aims to examine the effect of the Reflection-Based Questioning Approach (RBQA) on junior high school students' reading abilities. Using a quasi-experimental design, 66 eighth-grade students in Sidoarjo were divided into experimental and control groups. Data collected from reading tests were analyzed via an independent sample t-test. Findings revealed that the experimental group achieved a significantly higher mean post-test score (M = 89.45) than the control group (M = 78.83), with a significance value of 0.001. In conclusion, the RBQA strategy, utilizing the Initiate-Respond-Evaluate (IRE) model, significantly enhances students' reading comprehension skills compared to conventional methods.